Technical Analysis of Collapse in Tunnel Excavation and Suggestion of Preventing Appropriate Applicable Methods (Case Study: Sardasht Dam Second Diversion Tunnel) - Esmailzadeh, Akbar; Jafar Shirzad, Peyman; Shaffiee Haghshenas, Sina (Salehan Institute of Higher Education, 2017)
In order to either optimal use of water resource of KELAS river basin and electrical energy generation, Sardasht Dam and power plant are designed. Dam water diversion system includes two tunnels with inner diameter of 7 m. Several collapses have occurred in portal of second diversion tunnel (A2) which has created large cavity in tunnel crown. In order to prevent collapse, various ways such as steel sets installation and also grouting to increase strength of surrounded rock mass, are prescribed but none of technics could not to ban caving in. considering this fact that in order to continue tunnelling process, collapse zone should be passed, a solution or solutions must be suggested to overcome consecutive and dangerous collapses problem. In order to decrease tunnelling risks, in this research, using both experience and knowledge obtained from previous proposed executive solution to similar cases and technically analysis of occurred collapse in current diversion tunnel, it has been tried to suggest a new appropriate solution which defeat the problem. Finally, in order to stabilize of tunnel crown, as an effective and applicable solution, constructing retaining crown by means of rock bolts, was introduced.